The right to education and the resocialization of inmates in the penitentiary institution - Tapia Liendo, Gina Pamela (2021)
A study is carried out in order to analyze to what extent the right to education is guaranteed in the resocialization of inmates in the Pocollay de Tacna penitentiary establishment, 2019. The research is of basic type, non-experimental design, transversal, descriptive level, whose logical inductive method, allows reasoning starting from particular cases, to general knowledge. For the collection of information, the questionnaire, the interview and the analysis sheet were used as measurement instruments; which allowed collecting information and measuring the study variables. The sample consisted of 88 inmates and a manager of the Pocollay Penitentiary Center in Tacna. The results obtained made it possible to establish that: The right to education is guaranteed to a minimal extent in the resocialization of inmates in the Pocollay Penitentiary Establishment of Tacna, 2019.